The African Union's response to the Libyan crisis of 2011 - Twinomugisha, Wilson Kajwengye (My University, 2014)
The African Union is legally mandated by its Constitutive Act to intervene in security situations like the Libyan crisis of 2011, namely, to protect populations from genocide, war crimes and crimes against humanity, collectively known as mass atrocity crimes. In this respect, Article 4(h) of the AU Constitutive Act accords the right of AU “to intervene in a member State pursuant to a decision of Assembly in respect of grave circumstances, namely; war crimes, genocide and crimes against humanity.” When the Libyan crisis that had all the hallmarks of mass atrocity crimes broke out, African Union showed willingness to intervene and solve the crisis by passing resolutions, establishing fact finding missions, and, forming High Level Ad hoc committee comprising of 5 African Presidents and the AU Commission. However, when the time for reckoning came, AU was relegated to the periphery by NATO and other International actors in finding solutions to the Libyan crisis. This study therefore, examines and assesses the African Union’s response to the Libyan crisis of 2011 in light of the Article 4(h) of the Constitutive Act (intervention). The method of data collection majorly relied on what AU did in form of resolutions, Letters and other publications, and what has been written about AU’s actions in reference to the Libyan crisis of 2011. The study examined the measures AU took to respond to the crisis, the AU organs that were greatly engaged in looking for the solution to the crisis, and whether the measures undertaken were sufficient in resolving the crisis, and, in the hind sight what AU ought to have done. The study looked at the weaknesses that beset African Union in trying to look for a solution to the Libyan crisis, and concludes by proving recommendations for strengthening African Union Peace and Security Architecture to be able to confront head on, future African security crises like the Libyan one of 2011.
Thesis (M.M. (Security))--University of the Witwatersrand, Faculty of Commerce, Law and Management, Graduate School of Public and Development Management, 2013.
Keywords: African Union; Libya; Politics and government